Health, harm reduction, and social service providers' perspectives on the appropriateness and feasibility of peer distribution of HIV self-test kits among people who use drugs - Angela R. Bazzi; Chad J. Valasek; Tara Stamos-Buesig; William H. Eger; Alicia Harvey-Vera; Carlos F. Vera; Jennifer L. Syvertsen; Erik D. Storholm; Tyler S. Bartholomew; Hansel E. Tookes; Steffanie A. Strathdee; Heather A. Pines (BMC, 2024)
Abstract Background People who use drugs (PWUD) experience elevated HIV risk and numerous barriers to facility-based HIV testing. HIV self-testing (HIVST) could circumvent many of those barriers and is acceptable among PWUD, yet HIVST implementation for PWUD is limited. Service providers' perspectives on specific HIVST delivery strategies could help increase availability for PWUD. Methods From April-November 2021, we interviewed 16 health, harm reduction, and social service providers working with PWUD in San Diego, CA. Interviews and rapid thematic analysis explored perspectives on HIVST's utility and appropriateness, as well as the feasibility of and anticipated challenges with specific HIVST delivery strategies, including peer or secondary distribution. Results Participants viewed HIV as a significant threat to PWUD health and confirmed the presence of numerous barriers to local facility-based HIV testing. Participants viewed HIVST as a promising and potentially empowering solution. Based on community familiarity with secondary distribution of harm reduction supplies (i.e., naloxone) and information, participants viewed secondary distribution of HIVST kits as an appropriate and feasible strategy for increasing the reach of HIVST, but also described potential barriers (e.g., engaging socially disconnected individuals, ensuring linkages to services following HIVST) and provided suggestions for alternative HIVST kit delivery models (e.g., harm reduction vending machines). Conclusions Service providers viewed secondary distribution of HIVST kits among PWUD as promising, appropriate, and feasible, yet specialized efforts may be needed to reach the most marginalized individuals and ensure consistent provision of educational information and referral supports that maximize the impact of this approach.